Low energy availability is difficult to assess but outcomes have large impact on bone injury rates in elite distance athletes - Heikura, I. A.; Uusitalo, A. L. T.; Stellingwerff, T.; Bergland, D.; Mero, A. A.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
We aimed to (a) report energy availability (EA), metabolic/reproductive function, bone mineral density, and injury/illness rates in national/world-class female and male distance athletes and (b) investigate the robustness of various diagnostic criteria from the Female Athlete Triad (Triad), Low Energy Availability in Females Questionnaire, and relative energy deficiency in sport (RED-S) tools to identify risks associated with low EA. Athletes were distinguished according to benchmarks of reproductive function (amenorrheic [n = 13] vs. eumenorrheic [n = 22], low [lowest quartile of reference range; n = 10] versus normal testosterone [n = 14]), and EA calculated from 7-day food and training diaries (< or >30 kcal·kg-1 fat-free mass·day-1). Sex hormones (p < .001), triiodothyronine (p < .05), and bone mineral density (females, p < .05) were significantly lower in amenorrheic (37%) and low testosterone (40%; 15.1 ± 3.0 nmol/L) athletes, and bone injuries were ~4.5-fold more prevalent in amenorrheic (effect size = 0.85, large) and low testosterone (effect size = 0.52, moderate) groups compared with others. Categorization of females and males using Triad or RED-S tools revealed that higher risk groups had significantly lower triiodothyronine (female and male Triad and RED-S: p <.05) and higher number of all-time fractures (male Triad: p < .001; male RED-S and female Triad: p < .01) as well as nonsignificant but markedly (up to 10-fold) higher number of training days lost to bone injuries during the preceding year. Based on the cross-sectional analysis, current reproductive function (questionnaires/blood hormone concentrations) appears to provide a more objective and accurate marker of optimal energy for health than the more error-prone and time-consuming dietary and training estimation of EA. This study also offers novel findings that athlete health is associated with EA indices.